Baalbek-Heliopolis, the Bekaa, and Berytus from 100 BCE to 400 CE : A Landscape Transformed - Paturel, Simone, (Mnemosyne, Supplements, 2019)
The aim of this monograph is to understand the extent to which the landscape of Roman Berytus and the Bekaa valley is a product of colonial transformation following the foundation of Colonia Iulia Augusta Felix Berytus in 15 BCE. The book explores the changes observed in the cities of Berytus and Heliopolis, as well as the sites at Deir el-Qalaa, Niha, and Hosn Niha. The work fundamentally challenges the traditional paradigm, where Baalbek-Heliopolis is seen as a religious site dating from as early as the Bronze Age and associated with the worship of a Semitic or Phoenician deity triad and replaces it with a new perspective where religious activity is largely a product of colonial change.